Supervisi Akademik Kepala TK Terhadap Kinerja Guru Pada Masa Pandemi Covid-19 - A. Sri Mardiyanti Syam (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
Covid-19 pandemic that hit the whole world without exception, Indonesia devastated all aspects of life, including the education sector.  The government has swiftly changed the learning system to online at all levels of education, including early childhood education programs. The shift of the system requires the principal to participate in changing the strategy in order to continue to carry out its functions, including the function of academic supervision so that it can still ensure the ongoing quality of education in the institution.  The purpose of this study is to describe how the planning, implementation and evaluation of academic supervision is carried out by the principal of TK Al-Ikhsan Tomporeng Deceng in the midst of the Covid 19 pandemic. This study used a qualitative approach with an exploratory case study method. The research was conducted at TK Al-Ikhsan Tomporeng Deceng in the 2021/2022 academic year. The techniques of collecting data used were interview and documentation. The results showed that the implementation of academic supervision during the Covid 19 pandemic by the Principal of TK Al-Ikhsan Tomporeng Deceng continued well. This can be seen from 3 stages, including: (1) Planning: The principal arranged the form and timing of supervision during the pandemic and the instruments used. (2) Implementation: Checked the teacher's learning program, conducting class observations and held individual meetings (3) Evaluation: Provided feedback on the results of academic supervision so that teacher performance during this pandemic can be repaired or improved.